2020
DOI: 10.1055/s-0040-1701699
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Short-Term Effects of Compression Orthosis and Exercises in the Treatment of Pectus Carinatum: A Randomized Controlled Pilot Feasibility Trial

Abstract: Introduction Pectus carinatum (PC) is a congenital chest wall deformity which is characterized by the protrusion of the sternum and costal cartilages. Although orthotic and exercise therapies are commonly offered by physicians for PC treatment, there is a lack of evidence on the benefits of exercises and how long the orthosis should be worn. The aim of this study is to investigate the effects and feasibility of custom-made compression orthosis and exercises in the treatment of PC. Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Although COB is mentioned in international guidelines in the therapeutic algorithm for the treatment of PC, high-quality long-term data and a standardized wearing protocol are still not available [19][20][21]. Hunt et al confirmed the need for robust level I randomized data with a clearly standardized bracing protocol, objective measurement of outcomes, and recording of results at the end of the bracing treatment program in sufficiently powered sample sizes over a significant follow-up period [22].…”
Section: Discussionmentioning
confidence: 99%
“…Although COB is mentioned in international guidelines in the therapeutic algorithm for the treatment of PC, high-quality long-term data and a standardized wearing protocol are still not available [19][20][21]. Hunt et al confirmed the need for robust level I randomized data with a clearly standardized bracing protocol, objective measurement of outcomes, and recording of results at the end of the bracing treatment program in sufficiently powered sample sizes over a significant follow-up period [22].…”
Section: Discussionmentioning
confidence: 99%
“…Beginning from 1970's, patients with PC have been treated using compression braces that restore the normal thoracic shape by applying external compression over the thoracic wall. This method yielded predominantly favorable outcomes [10][11][12][13][14][15][30][31][32][33][34]. Nevertheless, treatment give-up rates due to noncompliance, in particular, were high and reached 40% in some studies [10,14,30].…”
Section: Discussionmentioning
confidence: 99%
“…Marcelo Martinez-Fero et al [4] stated that the physiotherapist lied in the center of non-surgical treatment, and was an essential member of the healthcare team for improvement of the posture. Giray et al [15] applied exercise treatment to 3 groups of patients during a period of one month. The groups used brace either for 8 hours, 23 hours, or not at all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample size was determined with GPower 3.1 software (Kiel University, Kiel, Germany) to achieve a 95% power ratio with a 0.05 margin of error within 95% confidence interval. Based on our calculations, we needed 8 patients in each group for a total of 16 patients [14,15] To increase mobility of the spine and thorax, manipulation and mobilization methods were applied to proper regions in vertebras, and mobilization was applied to sternocostal joints and area of protrusion. Additionally, postural awareness exercises were performed along with respiratory exercises, while standing in front of a mirror (10 minutes for each physiotherapy session).…”
Section: Methodsmentioning
confidence: 99%